Modified Okara improves Noodle Properties: Effects on digestibility, structure, and functionality - Guohong Tian; Meidan Li; Shuqi Xing; Laping He; Cuiqin Li; Shunbin Qiao; Ye Yuan; Taixun Luo (Current Research in Food Science)
This study developed a modified okara (the product of co-fermentation with Pleurotus ostreatus and Saccharomyces cerevisiae followed by cellulase treatment), evaluating its effects on noodle quality. Incorporation of 40 % modified okara significantly altered starch digestibility, reducing rapidly digestible starch (RDS) from 64 % to 50 %, while increasing slowly digestible starch (SDS) and resistant starch (RS) from 21 % and 6 % to 25 % and 14 %, respectively, which indicates a shift toward slower glucose release, beneficial for glycemic control. Structural characterization by FTIR, and SEM showed that okara promoted starch-protein-lipid complex formation and created porous networks that effectively encapsulated starch granules. These microstructural modifications were functionally significant, as dynamic rheological confirmed improved dough elasticity (G′ increased) at low okara concentrations. Additionally, soluble dietary fiber (SDF) content and ABTS radical scavenging ability increased to 9 % and 55 %, respectively, linked to liberated phenolics. These findings propose okara as a sustainable, functional ingredient for low-glycemic-index noodles, as it repurposes agro-industrial byproducts.